Sex-specific foraging behaviour is affected by wind conditions in a sexually size dimorphic seabird. (August 2020) - De Pascalis, Federico; Imperio, Simona; Benvenuti, Andrea; Catoni, Carlo; Rubolini, Diego; Cecere, Jacopo G.
Abstract : Flexibility in foraging behaviour is a key individual trait, promoting adaptive responses to changing environmental conditions. Such flexibility can be especially pronounced in marine predators that forage in highly dynamic environments and pursue ephemeral and patchily distributed prey. Individual characteristics, social interactions and resource availability may all promote behavioural flexibility, which in turn may foster divergence in foraging tactics within populations. The adoption of specific foraging tactics by individuals from the same population could be driven by a complex mixture of intrinsic and extrinsic factors. We GPS-tracked chick-rearing parents of a sexually size dimorphic, avian, marine top predator, the Scopoli's shearwater, Calonectris diomedea, across multiple foraging trips to investigate (1) intraindividual variation in foraging behaviour and (2) the effect of sex and wind conditions on the adoption of specific foraging tactics. Based on cluster analysis applied to GPS-derived behavioural patterns at the foraging trip scale, we identified variation in foraging trips, from fine- to coarse-scale foraging (FF and CF, respectively). FF trips were characterized by lower flight activity, shorter travel distances and more intensive prey-searching behaviour compared to CF trips. Individuals did not consistently perform FF or CF trips. Males were more prone to perform FF trips than females, but both sexes shifted towards CF trips with increasing wind intensity, probably to exploit the energetic advantages of dynamic soaring. We conclude that sex-specific foraging tactics reflect the interplay between sex-specific energetic optima, originating from differences in morphology and a reduction in the niche overlap between the sexes. By adopting flexible, sex-specific foraging tactics, shearwaters probably optimize their energy expenditure during the energy-demanding chick-rearing stage. Our study outlines the importance of both intrinsic and extrinsic factors in shaping interindividual variability in foraging behaviour. Highlights: Breeding shearwaters performed foraging trips with diverse food searching behaviour. Trips were classified as mainly involving coarse-scale or fine-scale foraging. Coarse-scale trips were mostly performed by females and with strong wind conditions. Sex differences were likely related to sex differences in morphology. Sex-specific foraging tactics could buffer intersexual competition for resources.